1975
DOI: 10.1146/annurev.ph.37.030175.001235
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Growth by Endocrines

Abstract: Normal growth is the product of a complex interaction among nutrition, .circulating hormones, and changing tissue responsiveness. Although malnutrition is probably the world's most common cause of poor growth, the greatest advances in our understanding of the growth process have come from studies of the function of endocrine factors in normal and disordered growth. Limitations of space have led us to give greatest attention to growth hormone and somatomedin because of the many recent developments in these area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
2

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(34 citation statements)
references
References 85 publications
2
30
0
2
Order By: Relevance
“…Furthermore, insulin has been noted to increase the incorporation of amino acids into the muscle and liver protein of fish (Tashima and Cahill, 1968;Lewander et al, 1976 (Bern etal, 1991;McCormick etal, 1992 (Plisetskaya, 1990;Sumpter et al, 1991 ). In mammals, growth hormone is less effective in the absence of insulin (Daughaday et al, 1975) and this may also be true in fish. The involvement of IGF and receptor of IGF in growth regulation in fish under the effects of insulin immersion should also not be excluded (Bern etal, 1991; Duan and Hirano, 1992;McCormick etal, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, insulin has been noted to increase the incorporation of amino acids into the muscle and liver protein of fish (Tashima and Cahill, 1968;Lewander et al, 1976 (Bern etal, 1991;McCormick etal, 1992 (Plisetskaya, 1990;Sumpter et al, 1991 ). In mammals, growth hormone is less effective in the absence of insulin (Daughaday et al, 1975) and this may also be true in fish. The involvement of IGF and receptor of IGF in growth regulation in fish under the effects of insulin immersion should also not be excluded (Bern etal, 1991; Duan and Hirano, 1992;McCormick etal, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis rates for various components of rat bone matrix are decreased by cortisone (6). Morphologic studies show that large doses of glucocorticoid suppress cell division in both bone and cartilage (17), and it has been suggested that glucocorticoids have a direct inhibitory effect on growing cartilage (7). Children on long-term corticosteroids may have retarded skeletal maturation (3) but the relationship between glucocorticoids, linear growth, bone age, and disease is complex (33).…”
Section: Speculationmentioning
confidence: 99%
“…According to the hypothesis of Salmon and Daughaday (1957), a number of the anabolic effects of growth hormone (GH) Van Wyk et al, 1974 ;Daughaday, Herington and Phillips, 1975a ;Hall and Luft, 1974 (Salmon and Daughaday, 1957). Amongst these are the bioassays using normal costal cartilage from fasted rats, rabbits and pigs and the pelvic rudiments of chick embryo (Yde, 1968 ;Bala, Hankins and Smith, 1975 ; Van den Brande and Du Caju, 1974a ;Hall, 1970).…”
Section: Somatomedin Definitionmentioning
confidence: 99%